2021
DOI: 10.1111/bjd.19891
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma‐associated glycosyltransferase GCNT2 as an emerging biomarker and therapeutic target*

Abstract: Summary In metastatic melanoma, with a dismal survival rate and propensity for treatment resistance and recurrence, it is critical to establish biomarkers that better predict treatment response and disease severity. The melanoma glycome, composed of complex carbohydrates termed glycans, is an under‐investigated area of research, although it is gaining momentum in the cancer biomarker and therapeutics field. Novel findings suggest that glycans play a major role in influencing melanoma progression and could be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 65 publications
1
1
0
Order By: Relevance
“…Sweeney and colleagues demonstrated that while normal epidermal melanocytes display abundant I-branches, these structures progressively diminish in primary and metastatic melanomas. This finding is in keeping with the inverse correlation between GCNT2 and melanoma progression reported by in silico and immunohistochemical analysis, suggesting that loss of GCNT2 expression could be used as a biomarker of melanoma [88]. Furthermore, this study clearly showed that knockdown of GCNT2 significantly enhances melanoma xenograft growth and three-dimensional colony formation and survival, whereas GCNT2 overexpression has the opposite effect.…”
Section: N-and I-glycan Branchingsupporting
confidence: 89%
“…Sweeney and colleagues demonstrated that while normal epidermal melanocytes display abundant I-branches, these structures progressively diminish in primary and metastatic melanomas. This finding is in keeping with the inverse correlation between GCNT2 and melanoma progression reported by in silico and immunohistochemical analysis, suggesting that loss of GCNT2 expression could be used as a biomarker of melanoma [88]. Furthermore, this study clearly showed that knockdown of GCNT2 significantly enhances melanoma xenograft growth and three-dimensional colony formation and survival, whereas GCNT2 overexpression has the opposite effect.…”
Section: N-and I-glycan Branchingsupporting
confidence: 89%
“…Aberrant glycosylation, indeed, plays an important role in melanoma cells, where it promotes a pro-invasive and/or pro-metastatic phenotype [ 10 , 11 ]. Several glycosyltransferases, enzymes responsible transferring specific glycans to proteins and lipids, showed abnormal abundances in metastatic cells, determining a corresponding abnormal amount of their enzymatic products [ 12 14 ]. Additionally, tumour hypersialylation promotes melanoma immune escape [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%